Interpretasi Metode Gauss-Seidel pada Sistem Persamaan Linier Fuzzy dengan Bilangan Fuzzy Sigmoid - Sa'adah, Maria Syifaus; Alisah, Evawati (Jurnal Riset Mahasiswa Matematika, 2024)
A system of linear equations can be combined with a fuzzy number that produces a new equation, namely a system of fuzzy linear equations. The system of fuzzy linear equations has the general form ,  as an element with real numbers, as a variable of fuzzy numbers, and  as a constant of fuzzy numbers. One kind of fuzzy number is sigmoid fuzzy number. The problem related to the system of fuzzy linear equations is how to solve the system of fuzzy linear equations. One method that can be used is using the Gauss-Seidel Method. This study aims to determine the results of the interpretation of the Gauss-Seidel Method to determine the solution of the fuzzy linear equation system. Based on the calculation results, it shows that the Gauss-Seidel Method does not always provide the right solution for fuzzy linear equation systems with fuzzy variables and constants in the form of sigmoid numbers expressed as cuts. The solution is considered correct if the substitution of the solution to the system of fuzzy linear equations and defuzzification  and  shows the same result.